A Federation of Online Labs for Assisting Engineering and Science Education in the MENA Region - Salah, Razwan Mohmed (2015)
Today, education is considered as a critical factor in the economic expansion and a principal component in any development strategy in third world countries. The main objective of developing education is to shape the students personality and bring them to the twenty-first century and understanding the nature of systems in which they work and live. Experiments in a hands-on laboratory for engineering and science fields are considered an essential backbone to improve students' skills. But actually, there are obstacles in a hands-on laboratory, for example: limitation of time, safety, scarcity of laboratory equipment, cost to setting up a new laboratory, etc. Nowadays, several online labs projects, which are controlled and executed via the Internet, are found to serve the students and the teachers, particularly in electric and electronic engineering subjects. These online experiments are similar to what happens in hands-on laboratories. Additionally, several advantages can be included from using the online labs, for example: safe environment, availability of experiments, and support the educational system. This Ph.D work shows the current status of higher education system in the Middle East and North Africa region and some of challenges that existed in their system. In addition, it highlights the cooperation and collaboration work among the researchers in this region, especially in the online labs fields. The methodology of work is described in this paper as well. Additionally, online labs federation and community of practice are suggested for assisting the higher education system in the Middle East and North Africa countries.